1991
DOI: 10.1161/01.cir.84.6.2336
|View full text |Cite
|
Sign up to set email alerts
|

Counter-regulatory responses to continuous and intermittent therapy with nitroglycerin.

Abstract: BACKGROUND Vasodilator therapy may be associated with reflex counter-regulatory responses, and these responses may play a role in the development of tolerance to nitroglycerin (GTN). METHODS AND RESULTS Standing systolic blood pressure, body weight, urinary sodium, and hormonal responses to continuous (n = 10) and intermittent (n = 10) transdermal GTN administration were studied in normal volunteers. There was rapid attenuation of the hypotensive respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(75 citation statements)
references
References 30 publications
2
72
0
1
Order By: Relevance
“…The Krebs and Krebs-HEPES solutions were gassed with carbogen (95% O 2 and 5% CO 2 ) and were of the following compositions (in mmol/L): NaCl 118, KCl 3.89, KH 2 PO 4 1.18, NaHCO 3 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Krebs and Krebs-HEPES solutions were gassed with carbogen (95% O 2 and 5% CO 2 ) and were of the following compositions (in mmol/L): NaCl 118, KCl 3.89, KH 2 PO 4 1.18, NaHCO 3 …”
Section: Methodsmentioning
confidence: 99%
“…However, the relevance of in vitro studies has been questioned because they exclude some factors that may be of importance to tolerance induction in vivo. 3 The data from in vivo animal studies are conflicting. Some studies using isolated vessels 21,23 or hemodynamic indices 24,25 have demonstrated that tolerance induction is associated with no cross-tolerance to non-nitrate sources of NO.…”
Section: Sage Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…35 In human subjects, by contrast, SNP fails to induce significant natriuresis, 37 and another SNP donor nitroglycerin even induces sodium retention and plasma volume expansion. 38 Thus, the role of NO/cGMP in adaptive natriuretic response to salt loading has been consistently confirmed in experimental animals but not human subjects. It is tempting to speculate that the contrasting effects of NO/cGMP on PT transport revealed in the present study may be at least partially responsible for these conflicting results.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study in normal subjects, the effect of continuous nitroglycerin patch application was studied to assess neurohormonal activation and reflex counterregulatory effects during nitrate therapy (Parker et al, 1991). The subjects were hospitalised in a clinical investigations unit and maintained on a diet with constant caloric, fluid, sodium, chloride and potassium intake.…”
mentioning
confidence: 99%